"You keep saying you are sorry". Exploring the use of sorry in customer communication on Twitter. (March 2021) - Lutzky, Ursula
Abstract: Customer service exchanges on social media have recently been described as taking place in "the Age of Sorry" (Segal 2018 ). In order to explore this claim further, this article studies the form sorry in the 6.4-million-word Airlines Twitter Corpus which includes tweets that customers directed at thirteen British and Irish airlines over a period of four months as well as the airlines' replies. It discusses the airlines' use of sorry in tweets which attempt to save face and maintain their reputation as reliable air travel providers. At the same time, the analysis explores the use of this form by customers, with a view to uncovering its metapragmatic potential and its perception as a communicative strategy for the legitimation of corporate activity. Embedded in the theoretical framework of discourse pragmatics, this study uses a corpus linguistic methodology to gain further insights into the form sorry and its communicative functions in the discursive construction of customer service online. The results show that airlines use sorry to a considerable extent to convey empathy rather than to apologise. Customers, on the other hand, tend to comment on airlines' use of the word and their reactions to airlines' tweets grant insights into the effectiveness of sorry as a communicative strategy. This study therefore contributes to an increased understanding of online service interactions and to enhancing customer communication on social media.